Accounting irregularities in financial statements: an analysis of public reprimand announcement / Emie Famieza Zainudin and Hafiza Aishah Hashim. - Zainudin, Emie Famieza; Hashim, Hafiza Aishah (Universiti Teknologi MARA Cawangan Selangor, 2016)
The issue of accounting irregularities in corporate reporting in Malaysia has caused a great deal of concern with respect to financial statement reliability. Bursa Malaysia Securities Berhad has publicly reprimanded companies that failed to comply with the Listing Requirements of Bursa Malaysia. The main objective of this study is to document the nature and extent of accounting irregularities involving public reprimand announcements. This study focuses on Malaysian public listed companies from 2007 to 2013. This study uses the classification system and documents five categories of violation under public reprimand announcements (i.e. (1) failure to make an immediate announcement on material facts on a timely basis; (2) failure to submit annual reports or late submission of annual or quarterly reports; (3) failure to take into account the adjustments/inconsistent amount of reported profit or loss with audited amount; (4) market manipulation or insider trading, and (5) questionable corporate exercises).